2010
DOI: 10.1371/journal.pone.0010443
|View full text |Cite
|
Sign up to set email alerts
|

Jnk2 Effects on Tumor Development, Genetic Instability and Replicative Stress in an Oncogene-Driven Mouse Mammary Tumor Model

Abstract: Oncogenes induce cell proliferation leading to replicative stress, DNA damage and genomic instability. A wide variety of cellular stresses activate c-Jun N-terminal kinase (JNK) proteins, but few studies have directly addressed the roles of JNK isoforms in tumor development. Herein, we show that jnk2 knockout mice expressing the Polyoma Middle T Antigen transgene developed mammary tumors earlier and experienced higher tumor multiplicity compared to jnk2 wildtype mice. Lack of jnk2 expression was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 48 publications
(57 reference statements)
5
50
0
Order By: Relevance
“…In a very elegant study, Sabapathy et al (48) showed that JNK1 was proproliferative via c-Jun phosphorylation, whereas JNK2 was antiproliferative through negative regulation of c-jun expression/phosphorylation and ubiquitin binding to c-jun. Furthermore, in a tissue type-and cell typespecific manner, JNK2 has an important role in regulating several molecules related to cell cycle progression checkpoints, especially under DNA damage conditions, leading to cell cycle arrest (69)(70)(71)(72). Hepatocytes from Jnk2 2/2 mice, however, exhibit increased proliferation rates compared with their wild-type counterparts (73), a finding in line with our results in HCC cells.…”
Section: Discussionsupporting
confidence: 86%
“…In a very elegant study, Sabapathy et al (48) showed that JNK1 was proproliferative via c-Jun phosphorylation, whereas JNK2 was antiproliferative through negative regulation of c-jun expression/phosphorylation and ubiquitin binding to c-jun. Furthermore, in a tissue type-and cell typespecific manner, JNK2 has an important role in regulating several molecules related to cell cycle progression checkpoints, especially under DNA damage conditions, leading to cell cycle arrest (69)(70)(71)(72). Hepatocytes from Jnk2 2/2 mice, however, exhibit increased proliferation rates compared with their wild-type counterparts (73), a finding in line with our results in HCC cells.…”
Section: Discussionsupporting
confidence: 86%
“…However, paradoxically, studies have demonstrated both a protumorigenic (16,41,42) and a tumor- (43,44) role for the JNK family, with duration of activation and context both implicated in defining the response (45). A major consideration in addressing these contrasting results is that reports of JNK acting as a tumor suppressor have studied the formation of primary tumors (46)(47)(48), where JNKmediated activation of apoptosis has an inhibitory role. In contrast, the in vivo screen described here represents an advanced tumor setting and our functional analyses confirm the complex interplay of prosurvival and proapoptotic signaling via JNK, which has important implications for the use of JNK inhibitors as potential therapeutics in cancer (12).…”
Section: Discussionmentioning
confidence: 99%
“…42 Increased p53 protein stability upon phosphorylation by JNK may be one important mechanism by which JNK signaling contributes to mediating oncogene-induced senescence and cell cycle arrest as a means to maintain genomic stability and to suppress tumorigenesis. 37,41 However, unlike jnk1 −/− mice, jnk2 −/− mice and mice harboring a specific deletion of mkk4 in keratinocytes were resistant to the 2-stage chemical carcinogenesis protocol. 43,44 Similarly, mice lacking JNK1 exhibited a marked decrease in gastric carcinogenesis induced by N-methyl-N-nitrosourea compared to their wild-type counterparts.…”
Section: Genetic Analysis Of Jnk Signaling In Cancermentioning
confidence: 99%